2018
DOI: 10.1038/s41416-018-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of isolated tumour cells in sentinel lymph nodes in early-stage breast cancer: a prospective study

Abstract: We conclude that presence of ITCs in the SNs is an adverse prognostic factor in early small node-negative breast cancer, and may be considered in the decision-making for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
6
6
0
Order By: Relevance
“…Our observations show that lymph node involvement is not dependent on the degree of tumor differentiation. Our findings confirm the observations of Tullberg et al concerning luminal A cancer [ 46 ] as well as studies conducted in breast cancers regardless of their molecular subtype [ 47 ]. On the contrary, Van Calster et al showed that tumor grade correlates with lymph node involvement in all subtypes of breast cancer [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations show that lymph node involvement is not dependent on the degree of tumor differentiation. Our findings confirm the observations of Tullberg et al concerning luminal A cancer [ 46 ] as well as studies conducted in breast cancers regardless of their molecular subtype [ 47 ]. On the contrary, Van Calster et al showed that tumor grade correlates with lymph node involvement in all subtypes of breast cancer [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that patient age does not correlate with lymph node involvement in this molecular subtype. These results are confirmed by other authors [ 33 , 46 , 47 ]. Surprisingly, Van Calster et al showed that the increase of patient age by 10 years reduces the chance of nodal involvement [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main advantage of this immunochemical method is to facilitate isolated tumor cell detection (<0.2 mm in diameter or 200 cells): isolated tumor cell detection increased by 35.2% when compared with histological examination according to Coleto et al (20). A recent prospective study of 936 pT1N0M0 breast cancer patients confirmed that isolated tumor cells in the sentinel lymph node were associated with unfavorable survival, justifying their detection by cytokeratin immunohistochemistry (40). In the present study, we defined positive nodal stage (pN+) by the presence of isolated tumor cells, micrometastases or macrometastases, whereas the pathologic nodal stage of breast cancer is still pN0 when only isolated tumor cells are present within the sentinel lymph node (18).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of large multicenter randomized controlled clinical study and long follow-up time, the impact of ITCs on patients' survival is controversial. Some studies showed that ITCs had little effect on prognosis (3)(4)(5)(6)(7)(8)(9), while other researches suggested that ITCs had an adverse influence on survival (10)(11)(12)(13)(14)(15). Therefore, more studies are urgently needed to confirm the realworld curative effect of lymph node ITCs in patients with female breast cancer (FBC).…”
Section: Introductionmentioning
confidence: 99%